The Design of Filling Online Certification Form for Teachers in Boyolali Regency (Case Study in Office of Youth, Education and Sports Boyolali Regency) - Ipung Sri Purwanti Hery (Journal of Indonesian Science Economic Research, 2020)
Development of the Information Technology world has made human life becomes increasingly mullah. Especially since, the creation of the internet, communication has become increasingly limited and without a hitch, both geographical barriers and time constraints. We can instantly communicate with family / relatives / friends who are in the other parts of the world directly through internet network. Easiness generated by the internet has also made the administrative process can be facilitated, especially in the process of filling Form Certification Program, Due to the existence of the internet has made possible the filling forms online Certification Program. Form making online applications, now has available a variety of programming language that support online applications, such as the ASP (Active Server Page), PHP (Hypertext Preprocessor), ColdFusion and Perl. In the implementation so far, charging Forms of Certification Program are still using manual system. This waste of time. It is also making admissions likely to be less conscientious because the number of teachers who have served is possibly experienced data error when the process of entering data into the database. When using the online system, teachers can do their own filing directly through computer that are available in laboratories, internet cafes and even from their respective homes This study seeks to improve the old system, a manual and replace it with a bare system. Replacement system is expected to save costs, specifically to (1) Review of the charging system Forms Certification Program is now running. (2) Make the MySQL database in a format to support the charging online form Certification Program (3) Make the necessary scripts in the process of filing the Registration Form Teacher with the PHP programming language. (4) System Certification Program online form filing. (5) The issues raised was related to matters of the charging system taken form the online certification Program.